“Sage” as a well-being indicator - Kohut, Dominik (Teorija in praksa, 2024)
The article considers the adequacy of GDP and its derivatives as well-being indicators, using the “SAGE” methodology that integrates “solidarity”, “agency” and “environment” into the economic metric. Applying this framework to Central and Eastern European countries, the research highlights significant variations in well-being indicators, pointing to the decoupling of economic well-being from social cohesion in certain countries in this region. While the Czech Republic experienced a reduction in solidarity, Slovenia consistently maintained high levels of solidarity and agency. The analysis suggests that incorporating broader dimensions into traditional metrics provides a more comprehensive view of the well-being of society.
Keywords: agency; blaginja; CEE; Družbeni kazalniki; indicators; kazalniki; Metodologija; Socialna država; solidarity; solidarnost; svoboda odločanja; well-being